A Comparative Study of Different Materials for Manufacturing of Miniature Spur Gears by Spark Erosion Wire Cutting Process - Chaubey, Sujeet Kumar; Gupta, Kapil; Jain, Neelesh Kumar (Applied Science and Engineering Progress, 2024)
Selection of suitable materials plays a key role in machining to produce durable and good quality micro parts and components as well as improve the productivity of machining processes. This paper presents the performance evaluation of Spark Erosion Wire Cutting (SEWC) for the manufacturing of miniature gears from different materials, namely stainless steel SS 304, aluminum 7075, copper, and brass. The major objectives of this performance evaluation of SEWC are to determine the effect of gear materials on the quality of the gears, the economic aspects of miniature gears, and the productivity of SEWC for fabricating miniature spur gears. The optimal range of SEWC parameters from past research works was considered for conducting experiments for this study. Four miniature spur gears were fabricated from each gear material. It was concluded from this study that 1) the use of SS 304 as miniature spur gear material results in a better surface finish than aluminum, copper and brass; 2) use of aluminum as miniature gear material is more productive than SS 304, copper and brass; 3) aluminum is more economical and material-efficient than SS 304, copper and brass to fabricate miniature gears by SEWC; 4) material lost in copper is higher as compared to other selected materials; and 5) cost of SS 304 miniature gear is more as compared to other fabricated gears by SEWC.